The durability of concrete produced from pozzolan materials as a partially cement replacement : A comprehensive review - Hamada, Hussein Mahmood; Abdulhaleem, Khamees N.; Majdi, Ali; Al Jawahery, Mohammed S.; Thomas, Blessen Skariah; Yousif, Salim T. (Elsevier Ltd, 2023)
Recently, the construction industry used innovative, cost-ecofriendly, and efficient materials in infrastructure development to mitigate the negative impact on the environment due to manufacturing Ordinary Portland cement (OPC). Many efforts have been conducted to improve sustainable materials to be used as cementitious material in pozzolanic materials such as fly ash (FA), slag, metakaolin (MK), rice husk ash (RHA), palm oil fuel ash (POFA), silica fume (SF), etc. Therefore, this paper introduced to review the results from previous studies that investigated the influence of waste materials with high pozzolanic materials on the numerous durability properties. The results show many advantages due to using those pozzolanic materials as partial cement replacements for the environment, saving energy and cost, and improving durability. Ground quartz and SF have the highest silica oxide (SiO2) content, it was recorded as higher than 90%, producing more pozzolanic activity than other waste materials. The resistance of the concrete containing POFA against acid and sulfate attacks increased when increasing POFA fineness. Besides, sorptivity values were reduced importantly for the blended concrete samples, the addition of 55% FA in binary blended concrete considerably reduced sorptivity of cement concretes. In addition to that, these pozzolanic materials improved other concrete properties. This paper can be a good base for researchers and construction players to adopt waste materials in improving the durability of concrete. Lastly, numerous possible studies were recommended for future studies.